Spectrum of Endoscopic Findings in Patients of Upper Gastrointestinal Bleeding at a Tertiary Care Hospital - Malghani, Waseem Sarwar (Cureus, 2019)
Background & aims Upper gastrointestinal bleeding (UGIB) is a common medical emergency that results in high patient morbidity and mortality. There are numerous causes of UGIB. The aim of our study was to evaluate the endoscopic findings in patients of UGIB in this part of the world. Methods This retrospective study was conducted at the Department of Gastroenterology Nishtar Medical University & Hospital Multan from June 2018 to March 2019. Record of all patients undergoing esophagogastroduodenoscopy (EGD) for evaluation of UGIB was reviewed. Data was entered and analyzed using SPSS version 20 (IBM, Armonk, NY, USA). Results Record of 730 (464 male and 266 females) patients undergoing EGD for UGIB was reviewed. Mean age of study population was 49.38 years with standard deviation of 14.86 years. Age of the youngest patient was 14 years while the oldest patient was 99 years of age. More than half of the patients (53%) belonged to the 41-60 years age group. The most common endoscopic finding was esophageal varices in 371 (50.8%) patients, followed by gastropathy (114, 15.6%), gastritis (68, 9.3%), cardio-fundal varices (58, 7.9%) and duodenal ulcer (26, 3.6%). Esophageal varices, gastritis, duodenal ulcers and gastric carcinomas were more likely to be found in male UGIB patients as compared to female patients (p = 0.039). Gastropathy, esophageal ulcer and gastric ulcer were more likely to be found in female UGIB patients. Esophageal varices and cardio-fundal varices were more likely to be found in UGIB patients from middle age group (p = 0.000). Whereas gastritis, duodenal ulcer, gastric erosions and duodenitis were more likely to be found in older (>60 years) UGIB patients (p = 0.000). Conclusion UGIB was more likely to occur in male gender. In our study, bleeding from esophageal varices was the most important cause of UGIB in this part of the world and bleeding from duodenal ulcer was quite uncommon as compared to the western world. Variceal bleeding had a significant association with male gender and middle age group patients. While duodenal ulcer bleed had a significant association with older age.